Bcl-2 delays cell cycle through mitochondrial ATP and ROS. Issue 7 (3rd April 2017) - Du, Xing; Fu, Xufeng; Yao, Kun; Lan, Zhenwei; Xu, Hui; Cui, Qinghua; Yang, Elizabeth
ABSTRACT: Bcl-2 inhibits cell proliferation by delaying G0 /G1 to S phase entry. We tested the hypothesis that Bcl-2 regulates S phase entry through mitochondrial pathways. Existing evidence indicates mitochondrial adenosine tri-phosphate (ATP) and reactive oxygen species (ROS) are important signals in cell survival and cell death, however, the molecular details of how these 2 processes are linked remain unknown. In this study, 2 cell lines stably expressing Bcl-2, 3T3Bcl-2 and C3HBcl-2, and vector-alone PB controls were arrested in G0 /G1 phase by serum starvation and contact inhibition, and ATP and ROS were measured during re-stimulation of cell cycle entry. Both ATP and ROS levels were decreased in G0 /G1 arrested cells compared with normal growing cells. In addition, ROS levels were significant lower in synchronized Bcl-2 cells than those in PB controls. After re-stimulation, ATP levels increased with time, reaching peak value 1–3 hours ahead of S phase entry for both Bcl-2 cells and PB controls. Consistent with 2 hours of S phase delay, Bcl-2 cells reached ATP peaks 2 hours later than PB control, which suggests a rise in ATP levels is required for S phase entry. To examine the role of ATP and ROS in cell cycle regulation, ATP and ROS level were changed. We observed that elevation of ATP accelerated cell cycle progression in both PB and Bcl-2 cells, and decrease of ATP and ROS to the level equivalent to Bcl-2 cells delayed S phase entry in PB cells. Our results support the hypothesis that Bcl-2 protein regulates mitochondrial metabolism to produce less ATP and ROS, which contributes to S phase entry delay in Bcl-2 cells. These findings reveal a novel mechanistic basis for understanding the link between mitochondrial metabolism and tumor-suppressive function of Bcl-2.